Criminal Penalty Execution Association - Jabr, Hakim; Hussein, Alaa Nasser Hussein (Journal of Legal Sciences, 2026)
The subject of the research is of great importance as it relates to the issue of regulating the rights and obligations included in the executive legal bond between its two parties represented by Its first party is the state, which is entrusted with the correctional administration and judicial authority that protects rights and freedoms, and its second party is the convict, Just as the state has the right to require punishment of the convict, it has the obligation to guarantee the legal status of the convict and the rights and freedoms it includes, guaranteed by the Constitution and the law, The convict is obligated to submit completely in accordance with the provisions of the law to implement the criminal penalty, while retaining all his rights and freedoms that were not deprived of him by the criminal judgment, and which he enjoyed like the rest of the members of society.  Ensuring that balance is achieved within the executive legal nexus requires that the party responsible for implementing punitive treatment methods not prejudice the legal status of the convict, Because implementation does not give the correctional administration the right to deprive the convict of his rights and cause him pain, but rather it exercises a role that is radically different from what it aimed to achieve in the previous era of punitive policy, Rather, in light of modern criminal and penal policy, it has become aimed at achieving reform and rehabilitation of the convict, and creating a sense of deterrence represented by the deprivation of part of his freedom and rights required to achieve his social integration with the rest of the members of society, in addition to not neglecting the concept of what criminal justice aims to achieve, Among its most important goals is the feeling of fairness and equality for the victim, his family, and members of society in the face of the law, in order to deter the previous roots that push towards revenge and revenge against the perpetrator.